Pemikiran Nasionalisme Paku Buwana X sebagai Sumber Pembelajaran Sejarah SMA (Studi Kasus di SMA Negeri 81 Jakarta) - Ervita Kurnia Sari; Lelly Qodariah; Eko Digdoyo; Suswandari Suswandari (Universitas Hamzanwadi, 2026)
This research background is based on the decline of nationalism values among students due to the influence of modernization. The aim of this study is to analyze the biography and life of Paku Buwana X, to analyze Paku Buwana X's nationalism thought, and to identify the application of Paku Buwana X's nationalism as a learning resource in SMA Negeri 81 Jakarta. The research method used is qualitative with a case study approach. Data collection techniques include interviews and observations. To test the validity of the data, source and method triangulation were employed. The subjects of this research are six eleventh-grade students. The results show that the values of nationalism taught and instilled by Paku Buwana X have positively shaped students' characters and patriotic spirit, especially through exemplification and real-life examples demonstrated by him. Furthermore, critical analysis reveals that stories and experiences of Paku Buwana X can serve as effective media to enhance patriotism and national awareness among students. These findings are expected to contribute to the development of nationalism-based learning models in high schools, as well as to strengthen the role of national figures as sources of inspiration and character education in schools. The study also recommends maximizing narrative approaches involving figures like Paku Buwana X as part of character and nationalism education strategies in the modern era.